POLITIK HUKUM PERADILAN PAJAK DALAM SISTEM PERADILAN DI INDONESIA - Zulfikar, Muhammad Nahyan; Adabi, Muhammad Ikhwan; Muharrir, Muharrir (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
AbstractThe problematic legal arrangement of the tax court as stipulated in Article 5 paragraph (1) and paragraph (2) of Law number 14 Year 2002 on Tax Court, paragraph (1) "Technical judicial guidance for the Tax Court is carried out by the Supreme Court and paragraph (2) Organisational, administrative, and financial guidance for the Tax Court is carried out by the Ministry of Finance (now Ministry of Finance). This is certainly different from the independent judicial system or what is known as the "one roof system" in Law number 48 of 2009 concerning Judicial Power. This research uses a juridical-normative legal research method. The Juridical-Normative approach uses methods and techniques through a statute approach, case approach to examine the separation of powers and checks and balances of two power institutions, which attributively regulate the position of the Tax Court with the Tax Court Law and the Judicial Power Law and examine the Constitutional Court's decision relating to the discussion of the legal issues studied. The results of an in-depth study of the legal politics of the establishment of the Tax Court Law, should be directed at efforts to establish an independent judicial system "one roof system" and the Constitutional Court's decision to grant and declare Article 8 paragraph (2), Article 8 paragraph (3) and Article 13 paragraph (1) of the Tax Court Law does not have binding legal force, in maintaining the spirit of independent judicial power so that the court does not become an instrument of power (machtsapparaat), but becomes an instrument of law (rechtsapparaat), it is necessary to revise the Tax Court Law as part of improving the separation of powers and cheks and balances.Keywords: Legal Politics, Tax Court, Separation of Powers, checks and balances